The comparison of perendoscopic injection therapy with medical treatment in Forrest’s II ulcers: Pilot study - Murat SARUÇ; Feyzullah GÜÇLÜ; Sabriye ÖZKAYA; Nurten KÜÇÜKMETİN and Hakan YÜCEYAR (Turkish Journal of Gastroenterology, 2019)
-